2020
DOI: 10.1093/infdis/jiaa332
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 Expression Is Increased in the Lungs of Patients With Comorbidities Associated With Severe COVID-19

Abstract: Patients who died from COVID-19 often had comorbidities, such as hypertension, diabetes, and chronic obstructive lung disease. Although angiotensin-converting enzyme 2 (ACE2) is crucial for SARS-CoV-2 to bind and enter host cells, no study has systematically assessed the ACE2 expression in the lungs of patients with these diseases. Here, we analyzed over 700 lung transcriptome samples from patients with comorbidities associated with severe COVID-19 and found that ACE2 was highly expressed in these patients com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
285
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(309 citation statements)
references
References 45 publications
10
285
0
1
Order By: Relevance
“…Emerging evidence indicates high-risk individuals with SARS-CoV-2 have high rates of alveolar epithelial type 2 (AT2) cell infection, suggesting disease severity may be related to higher alveolar expression of the SARS-CoV-2 receptor angiotensin converting enzyme (ACE2) and its co-receptor transmembrane protease/serine subfamily member 2 (TMPRSS2) 8,9 . In fact, a recent meta-analysis of 700 people with predicted COVID-19 co-morbidities found that their lungs expressed high levels Ace2 mRNA 10 . ACE2 is a zinc containing metalloprotease present at the surface of cells in the lung, heart, intestines, kidneys, and brain.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence indicates high-risk individuals with SARS-CoV-2 have high rates of alveolar epithelial type 2 (AT2) cell infection, suggesting disease severity may be related to higher alveolar expression of the SARS-CoV-2 receptor angiotensin converting enzyme (ACE2) and its co-receptor transmembrane protease/serine subfamily member 2 (TMPRSS2) 8,9 . In fact, a recent meta-analysis of 700 people with predicted COVID-19 co-morbidities found that their lungs expressed high levels Ace2 mRNA 10 . ACE2 is a zinc containing metalloprotease present at the surface of cells in the lung, heart, intestines, kidneys, and brain.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, ACE2 mRNA levels also appear to be regulated by a multitude of factors, including age (11), tobacco smoke (12), and other respiratory tract infections (e.g., rhinovirus and influenza virus) (9) potentially via the canonically antiviral type I and II interferon (IFN) pathways (9,12,13). Thus, a tempting hypothesis that remains to be experimentally validated is that external or biological factors leading to enhanced ACE2 expression may exacerbate SARS-CoV-2 replication and/or expand its cellular tropism (14), thereby increasing the severity of COVID-19 in individuals of certain risk groups, including the elderly, smokers, and those with coinfections or comorbidities (15).…”
mentioning
confidence: 99%
“…Chromatin immunoprecipitation sequencing (ChIP-seq) showed that EZH2 depletion induced H3K27me3 decrease, with concomitant H3K27ac increase, at ACE2 promoter in human ESCs (Li Y. et al, 2020). The role of H3 methylation and acetylation in the epigenetic regulation of ACE2 was also hypothesized by Pinto et al, who demonstrated that co-morbidities such as hypertension, diabetes, and chronic obstructive lung disease increase ACE2 transcription in the lung (Pinto et al, 2020).…”
Section: Transcriptional Post-transcriptional and Post-translationamentioning
confidence: 87%